(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2023)
Constructive criticism in colleges is a practice that proposes a critical view of controversial issues with the aim of improving understanding and existing conditions. Research aims to determine the role of citizenship education in colleges in helping students use controversial trends wisely, develop critical abilities, and encourage reflective thinking that can contribute to social development and improvement. This research method uses qualitative and descriptive methods. The research participants consisted of students from various study programs and educational levels at several Tasikmalaya colleges. As for the results of this study, five indicators of constructive criticism show the role of citizenship education in managing student controversy: (1) ability to deliver constructive criticism; (2) response to criticism; (3) active listening skills; (4) ability for effective feedback; and (5) collaboration and problem solving.